Reusable learning objects for nurse education: development, evaluation, challenges and recommendations. - Khan, Ehsan; Tarling, Maggie; Calder, Ian (British Journal of Nursing, 2019)
Online resources are expected within healthcare education, and a plethora of online or technology-based delivery methods are available. Reusable learning objects (RLOs) are a form of digitally supported education that can be used multiple times in various locations; they are especially favoured by nurses. Little is understood about the issues involved in their creation. This article examines the development of an RLO in respiratory physiology for first-year nurses and how those creating it worked together. Feedback during the development of the RLO was gathered over 1 year from academics, technologists and students. Issues that arose included variations and misunderstanding regarding terminology and academics' not appreciating the time it took to develop the resource and its potential. Practical matters included sourcing royalty-free or in-house images, record-keeping and version control, and addressing production logic in case developers moved to other projects. It is important to include students during the design process rather than in just evaluating the final product because user experience and navigation have to be considered together with pedagogical content. Addressing these issues when developing an RLO will help streamline the process and generate a student-focused output.